Exposure to various benzene derivatives differently induces cytochromes P450 2B1 and P450 2E1 in rat liver - Gut, I; Terelius, Y; Frantík, E; Linhart, I; Soucek, P; Filipcová, B; Klucková, H (Archives of toxicology, 1993)
Benzene (B), toluene (T), ethylbenzene (EB), styrene (S) and xylene isomers (oX, mX, pX) are important environmental pollutants and B is a proved human carcinogen. Their inhalation by male Wistar rats (4 mg/l, 20 h/day, 4 days) caused cytochrome P450 (P450) induction. The degree of P450 2B1 induction increased and that of 2E1 decreased in the series B, T, EB, S, oX, mX and pX, as estimated by Western blots, while neither solvent was as effective for 2B1 induction as phenobarbital and B was more effective for 2E1 than ethanol. The levels of several other P450s decreased after exposure to these solvents, B being most effective. Exposure to these solvents increased in vitro hepatic microsomal oxidation of B and aniline (AN) (2E1 substrates) 3 to 6-fold, indicating induction of this P450. T oxidation was increased 2 to 4-fold and chlorobenzene (ClB) oxidation 3-fold. Sodium phenobarbital (PB, 80 mg/kg/day, 4 days, i.p.) did not increase ethylmorphine (EM) and benzphetamine (BZP) demethylation (2B1 substrates), neither of the B derivatives did so, and oX decreased it; however, pentoxyresorufin O-dealkylation was well related to the immunochemically detected 2B1 levels in control, PB and B microsomes. PB did not increase B, but increased T and ClB oxidation 2-4 and 3-fold, respectively, indicating possible 2B1 role in their oxidation. B oxidation after various inducers was related to immunochemical 2E1 levels, T and ClB oxidation to both 2B1 and 2E1 and AN oxidation to 2E1 and 1A2 levels.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: jaterní mikrozomy; Microsomes, Liver; Xylenes; xyleny; krysa rodu Rattus; Toluene; Benzene; zvířata; Cytochrome P-450 CYP2E1; benzen; Oxidoreductases, N-Demethylating; potkani Wistar; toluen; oxidoreduktasy; Cytochrome P-450 Enzyme System; enzymová indukce; Rats, Wistar; Male; cytochrom P-450 CYP2E1; N-demethylasy; cytochrom P-450 CYP2B1; Rats; Cytochrome P-450 CYP2B1; Animals; mužské pohlaví; Oxidoreductases; systém (enzymů) cytochromů P-450; Enzyme Induction